IMPLEMENTATION OF MURABAHAH CONTRACTS IN OWNERSHIP FINANCING A HOUSE IN THE SHARIA STATE SAVINGS BANK, LHOKSEUMAWE CITY - Srik Wardani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Home ownership loans are home financing from Bank BTN for the purposes of buying a house from a developer or non-developer, both for buying a new or second home, buying a ready-to-live-in house (ready stock) or not finished (indent) or taking over credit from other banks. Research This research aims to find out how the murabahah contract is applied to home ownership financing at the Lhokseumawe Syariah State Savings Bank. The type of research used in this research is descriptive qualitative research. The data in this study were obtained from secondary data sources and primary data. Data collection techniques used in this study is by observation, interviews, and documentation. The results of this study are that home ownership financing at BTNS Lhokseumawe already uses a murabaha contract,but the Bank also uses a wakalah contract as a murabahah companion contract.